The Great Depression. - World Book, Inc. (Chicago World Book, 2011)
"A history of the Great Depression, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.
What was the Great Depression? -- The roaring twenties -- Haves and have-nots -- Down on the farm -- Risky bets -- The crash -- Credit and debt -- Bank failures -- The collapse of world trade -- Unemployment -- President Hoover -- Hoovervilles and hobos -- Hunger and food marches -- The bonus army -- FDR-the people's choice -- The president's first move -- The New Deal -- Working towards recovery -- Opposition to the New Deal -- The second New Deal -- The Dust Bowl -- Making do -- Keeping the spirits up -- Cultural programs -- Crime -- The Depression in the U.K -- The Depression in Europe -- It ends in war -- Timeline.
Keywords: New Deal, 1933-1939 -- Juvenile literature; Depressions, 1929 -- United States -- Sources -- Juvenile literature; New Deal, 1933-1939 -- Sources -- Juvenile literature; United States -- History -- 1933-1945 -- Juvenile literature; United States -- History -- 1919-1933 -- Juvenile literature; United States -- Politics and government -- 1933-1945.; Depressions, 1929 -- United States -- Juvenile literature; United States -- Economic conditions -- 1918-1945 -- Juvenile literature; United States -- History -- 1933-1945 -- Sources -- Juvenile literature; United States -- History -- 1919-1933 -- Sources -- Juvenile literature; United States -- Economic conditions -- 1918-1945 -- Sources -- Juvenile literature